Blocking probability analysis of wireless sensors that employ opportunistic spectrum access - L. Anusha; B Seetha ramanjaneyulu; K. Annapurna (JOIV : International Journal on Informatics Visualization, 2017)
Opportunistic accessing of vacant channels of licensed spectrum by non-licensed wireless devices offers a convenient solution to the spectrum scarcity problems experienced by many wireless communication systems. Due to the fixed assignment policy of spectrum, some of the licensed frequencies are not in full utilization by their licensed users. On the other hand, there exists a severe scarcity of bandwidth for new wireless services. In this context, opportunistic access is found to be a boon, to overcome the spectrum scarcity problems. In this paper, opportunistic accessing of vacant channels by the wireless sensors is analysed. Finding the number of devices that can be supported for the available vacant bandwidth is the main focus of the work. Assessing the blocking probabilities experienced by the devices is found to offer an approximation of the number of devices that can be accommodated in a given scenario, for permissible blocking rates. This kind of analysis can help in proper planning of such wireless sensor networks, to deploy them in a way that they can make use of the white space bandwidths efficiently.